Caring Behaviors as Perceived by Both Nursing Students and Pregnant Women during the Stage of Labor: A Comparison Study - Kampan, Sasitorn; Saetan, Chuttikarn; Damchuti, Inghathai (Princess of Naradhiwas University Journal, 2019)
This research aimed to: 1) study caring behaviors of nursing students as perceived by themselves, and pregnant women, and 2) compare the perceptions between the nursing students, and the pregnant women. The sample consisted of 72 third-years nursing students, and 72 pregnant women. The research instrument was aquestionnaire about caring behaviors of nursing students during the stage of labor, as perceived by both the nursing students, and the pregnant women. Its reliability was tested using Cronbach’s alpha coefficient, yielding values of .96 and .97, respectively. The data were analyzed by using percentage, mean, standard deviation, and t-test. The research found that: 1) the level of caring behavior of the nursing students as perceived by the pregnant women was at a very high level ( = 4.70, S.D.=.32) , and the level of caring behavior of the nursing students as perceived by themselves was at a high level ( = 4.35, S.D. = .40) , and2) the caring behaviors perception in perinatal period, according to the nursing students, was not different from the pregnant women’s perception